The development of mosque library in Nigeria: the southwest perspective - Akinwande, Kazeem Abiodun; Bello, Onifade Abdurrahman; Hashim, Roosfa (Diva Enterprises PVT LTD., 2019)
Mosque library is as important as every other type of library. This is because mosque library is essential for the preservation of books and other resources on religion and facilitates learning of religious ethics, guides, practices and norms. If they are well developed and manged, they can held to prevent immoral and other social vices which Islam forbids. With the availability of a mosque library, Muslims can always go to this library to satisfy their religious and mundane information needs without being exposed to the immoral/haram activities that they are likely to encounter in other public, national, academic and some other type of library. This study aims to find out the awareness of southwestern Nigerians about mosque library, its existence in the region, level of use and challenges militating against its development.